Pengaruh Kegiatan Finger Painting Terhadap Kemampuan Motorik Anak Usia dini 4-5 Tahun di Tk Shafa Islamic Karawang - Durin Nafiatin; Astuti Darmiyanti; Feronica Eka Putri (Peneliti.net, 2022)
Through finger painting exercises, this study hopes to improve kids' fine motor skills. With a sample of 15 group A children aged 4-5 years old, this study used an experimental methodology with a one group pretest-posttest design. In group A of the Kindergarten Shafa Islamic Karawang, this study was carried out ten times. The findings of this study show that fine motor abilities increased by 24 during the pretest and by 51 during the posttest. Additionally, as can be seen from the Paired Sample T-Test Table results, where the T-count value is 2,145 with sig. (0.000), it can be deduced from the data that finger painting activities have a significant impact on kids between the ages of 4-5.